Annual Report on Exchange Arrangements and Exchange Restrictions 1975. (Annual Report on Exchange Arrangements and Exchange Restrictions, 1975)
This paper discusses that although in terms of value world trade increased at a sharp rate, the rise was in only a small degree due to an expansion in the volume of trade. Because of the inflation and the sharp increase in the prices of oil and some other primary products, the value of world trade, rose by some 45 percent or nearly double the rate of growth in 1973. As a result of a steep upward movement of commodity prices in 1973, the terms of trade of the developing countries and other primary producing countries had improved substantially in that year, while those of the industrial countries had been unfavorably affected. In 1974, a tendency toward reversal of these shifts in terms of trade, together with the increase in the price of oil, resulted in a considerable deterioration in the terms of trade of the non-oil producing developing countries and of other primary producing countries. Reduced rates of increase in export volumes also affected the international payments positions of these two groups of countries in 1974.